2001
DOI: 10.1084/jem.194.4.541
|View full text |Cite
|
Sign up to set email alerts
|

Cd47 (Integrin-Associated Protein) Engagement of Dendritic Cell and Macrophage Counterreceptors Is Required to Prevent the Clearance of Donor Lymphohematopoietic Cells

Abstract: Integrin-associated protein (CD47) is a broadly expressed protein that costimulates T cells, facilitates leukocyte migration, and inhibits macrophage scavenger function. To determine the role of CD47 in regulating alloresponses, CD47+/+ or CD47−/− T cells were infused into irradiated or nonconditioned major histocompatibility complex disparate recipients. Graft-versus-host disease lethality was markedly reduced with CD47−/− T cells. Donor CD47−/− T cells failed to engraft in immunodeficient allogeneic recipien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
166
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(179 citation statements)
references
References 24 publications
(37 reference statements)
8
166
1
Order By: Relevance
“…Pretreatment of mice with clodronate-loaded liposomes reduced significantly both the number of splenic CD11b þ macrophages and apoptotic cell-induced donor BM engraftment ( Figure 1c). As described previously, 33 we observed that not all splenic DC subsets were depleted by clodronate-loaded liposome infusion due to their anatomic location (Supplementary Figure 1 online). To further explore the role of host DC in the graftfacilitating effect of apoptotic cells, a transgenic mouse model for in vivo DC ablation 34 was used.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Pretreatment of mice with clodronate-loaded liposomes reduced significantly both the number of splenic CD11b þ macrophages and apoptotic cell-induced donor BM engraftment ( Figure 1c). As described previously, 33 we observed that not all splenic DC subsets were depleted by clodronate-loaded liposome infusion due to their anatomic location (Supplementary Figure 1 online). To further explore the role of host DC in the graftfacilitating effect of apoptotic cells, a transgenic mouse model for in vivo DC ablation 34 was used.…”
Section: Resultssupporting
confidence: 72%
“…To deplete resident host phagocytes, liposomes loaded with clodronate 32,33 were infused before BMT. Pretreatment of mice with clodronate-loaded liposomes reduced significantly both the number of splenic CD11b þ macrophages and apoptotic cell-induced donor BM engraftment ( Figure 1c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of macrophages for anti-CD47 antibody-mediated anti-tumor effects was reported in previous studies wherein immunocompromised mice lacking T cells, B cells and NK cells rapidly eliminated transplanted CD47-deficient hematopoietic cells or human AML cells, but this elimination was blocked following the depletion of macrophages. 12,33 The bone marrow microenvironment is critical for myeloma cell survival and proliferation. [34][35][36][37] In addition, the bone marrow microenvironment has been reported to protect myeloma cells from chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23] CD47 is highly expressed on RBCs, but ubiquitously expressed by most cells in the body, and can also negatively regulate phagocytosis of platelets and leukocytes. [24][25][26] The amount of CD47 on the cell surface regulates macrophage phagocytosis, since IgG-opsonized RBCs from CD47 ϩ/Ϫ mice (expressing about 50% of normal levels of CD47) are taken up faster than wild-type (WT) RBCs, but slower than CD47 Ϫ/Ϫ RBCs. 27 We have shown that the phagocytosis-inhibitory effect of CD47 does not come into play on apoptotic nucleated cells, where CD47 is clustered into patches on the apoptotic cell surface and segregated away from prophagocytic ligands such as PS or calreticulin.…”
Section: Introductionmentioning
confidence: 99%